Tinjauan Yuridis terhadap Risiko Perbankan dalam Layanan Letter of Credit - Muhammad Hanif Asror; Umi Khaerah Pati (Universitas Sebelas Maret, 2024)
Along with the rapid development of trade between countries, Letter of Credit (L/C) is a form methods within overcoming the payment system carried out by the parties. This must also be accompanied by an anticipatory attitude, therefore there are also many irresponsible parties by utilizing the opportunity as a means to gain profits in an improper way that also harms many other parties. The bank as an important player in the implementation of the L/C must anticipate the banking risks that arise in order to run well. Therefore, this article aims to analyze the review through the application of law in L/C services to banking risks. This type of research is normative research. The data sources used are primary data sources and secondary data sources and the delivery of data is written descriptively. If one party is dissatisfied because the other party fails to fulfill its obligations under the agreement, the dissatisfied party will receive legal protection as outlined in the regulations governing L/C in both international and national laws. Protection is derived from regulations that typically oversee L/C, such as the Uniform Customs and Practice for Documentary Credit (UCP), Bank Indonesia Regulations, and internal regulations. The primary focus is on recognizing L/C as banking risks designated by the central bank, along with risk management based on internal banking policies and in line with the international practices of UCP.